(untitled) (CIPEEX, 2025)
WattStatus is a software developed to calculate and manage energy consumption, promoting conscious usage and assisting both individuals and organizations in reducing their energy costs. The system also aims to generate a positive impact on the environment by encouraging sustainable practices. Utilizing agile methodology and the Scrum framework, the development team sought to enhance the software’s interface, improve user interaction, and provide relevant and accessible content. The method employed involved creating a detailed product backlog and using user stories to ensure the software met users’ needs and expectations. These stories helped direct the development of features that not only facilitated energy control and savings but also promoted environmental awareness. Continuous improvements focused on providing an intuitive and efficient user experience, making the software an effective tool for energy management. The results obtained during development indicated that WattStatus has the potential to positively impact social and environmental spheres. Through accurate calculations and interactive tools, the software empowers users to adopt a more sustainable lifestyle, reducing their energy costs and contributing to environmental preservation. The team successfully built and refined the software based on ongoing user feedback and performance metrics, ensuring that the application met both technical expectations and usability standards. In conclusion, WattStatus represents a significant step towards a more sustainable future. The software combines reliable calculations with personalized interactive features to promote energy savings and encourage sustainable practices. The continuous pursuit of improvements in interface design, user interaction, and content availability demonstrates the team’s commitment to providing an effective and impactful tool. With strategic partnerships and a continuous focus on usability, WattStatus aims to engage both individuals and businesses in the cause of energy conservation and sustainable development.